Conservation and utilization of crop genetic resources in Malaysia: Mardi’s Effort - Nordin, Mohd Shukor (David Publishing Company., 2015)
Abstract: Malaysian Agriculture Research and Development Institute (MARDI) is the country’s major custodian of the nation’s crops genetic resources. It has a global responsibility in the conservation of genetic resources of banana, sweet potato and citrus, and national responsibility for the conservation of crops, such as rice, tropical fruits and some herbs and medicinal plant species. MARDI rice seed genebank at Seberang Prai in the state of Penang was established in 1984 and currently holds 12,770 registered rice accessions, of which 53% are of local origin. In addition, MARDI also conserves genes in the field, mostly for underutilized tropical fruit genetic resources. At present, about 168 species of underutilized, rare and wild tropical fruit species consisting of about 2,000 accessions, the largest in the country, are being conserved. The species include “kuini” (Mangifera odorata), “bacang” (Mangifera foetida), “binjai” (Mangifera caesia), “cerapu” (Garcinia praniana), “rambai” (Baccaurea motleyana), “asam gelugor” (Garcinia atroviridis), “terap” (Arthocarpus odoratissimus) and “pulasan” (Nephellium rambutan-ake). The accessions are mostly conserved ex situ in field genebanks located at the various MARDI stations throughout the country. Although the conservation of the various crop species genetic resources is important, the real challenge is enhancing its utilisation. The main objective of the paper was to share and disseminate information related to works conducted and strategies opted by MARDI on the conservation and utilization of crop genetic resources. Information on species of crops that are available in MARDI’s genebank was also highlighted together with brief information of some of the associated traits of significant importance posses by those genetic resources.